Finite Element Analysis for Crack Width and Deflection Control in Reinforced Concrete Floor Systems at Serviceability Limit State - Dien Nguyen (Journal Innovation of Civil Engineering (JICE), 2026)
Serviceability performance is crucial for reinforced concrete (RC) structures to ensure durability, functionality, and user comfort. While existing research often focuses on individual components, integrated evaluations of complete slab-beam floor systems using practical finite element analysis (FEA) in accordance with Eurocode 2 remain limited. This study evaluates the short-term and long-term serviceability performance of a typical RC floor system (top/bottom slabs, main/secondary beams) under service loads. A 3D finite element model was developed using SAFE software, with crack-width and deflection verifications conducted in accordance with Eurocode 2 (EN 1992-1-1) and Eurocode 0 (EN 1990). The numerical results confirm that all structural components satisfy the prescribed serviceability limits: Maximum Crack Width, measured at 0.085 mm for the main beam and below 0.22 mm for the slabs, both well within the 0.30 mm allowable limit. Maximum Long-Term Deflection: Reached 27.6 mm for the main beam, remaining below the 34.0 mm allowable limit. The FEA successfully captured realistic slab-beam interactions and internal force redistributions, providing structural engineers with practical, code-compliant guidance. Keywords: Reinforced Concrete; Serviceability Limit State; Crack Width; Deflection; Eurocode 2; FEM.